Independent Curriculum: Correlation Between Science Process Skills and Cognitive Abilities with Students' Caring Attitudes in Junior High Schools - Hikmawati Hikmawati; Aris Doyan; Supriadi; Rohani (International Journal of Contextual Science Education, 2025)
This study aims to explore the relationship between science process skills, cognitive abilities, and students' caring attitudes in the context of project-based learning in the Independent Curriculum era. The project implemented is the processing of plastic waste into eco-friendly bricks stools, which is also part of the Pancasila Student Profile Strengthening Program with the theme of a sustainable lifestyle. This study uses a quantitative approach with a correlational design. Data were obtained from 86 seventh grade students at SMP Negeri 16 Mataram. The research instruments included a science process skills test, a cognitive ability test, and a caring attitude questionnaire. The results of the Pearson Correlation test showed that science process skills had a significant relationship with cognitive ability (r = 0.992). The results of the Kendall's tau-b Correlation test showed that science process skills had a significant relationship with caring attitude (τb = 0.798) and caring attitude had a significant relationship with cognitive ability (τb = 0.889). In other words, it can be said that project-based learning can improve science process skills and cognitive ability while building a character of caring attitude towards the environment. Therefore, it can be concluded that the implementation of project-based learning in the Independent Curriculum, such as making stools from eco-friendly bricks, has a positive impact on developing science process skills and cognitive abilities as well as students' caring attitudes. Project-based learning can be an alternative innovative model to be implemented at various levels of education so that efforts are needed to train teachers in implementing this learning model, and support from schools and government policies to improve the sustainability of environmental-based education.